Biochar and liquid fertilizer differently affect bulk density of Spodosols and Ultisols - Hartati, Wahjuni; Sherlyani, Stella; Syahrinudin, Syahrinudin; Sudarmadji, Triyono (Fakultas Kehutanan Universitas Mulawarman, 2025)
Ultisols and Spodosols are soils with contrasting properties - Ultisols are clay-rich while Spodosols are sand-dominated. Soil bulk density, which can limit fertility, is an important property needing improvement in these degraded soils. This study aimed to determine how applying biochar combined with liquid fertilizer affects the bulk density of these soils. The research design was a Randomized Complete Block Design (RCBD) with biochar application set as the research factor and length of biochar soaking in liquid organic fertilizer (LOF) set as the research block. Bulk density sampling occurred at three moisture levels - mornings, afternoons, and evenings after watering. Overall, the two soil types responded differently to biochar treatment. Immersion duration and moisture level at sampling did not significantly impact bulk density